Mutu Fisik, Mutu Giling dan Mutu Fungsional Beras Varietas Lokal Kalimantan Barat - Indrasari, Siti Dewi; Rakhmi, Ami Teja; Subekti, Agus; Kristamtini, Kristamtini (Jurnal Penelitian Pertanian Tanaman Pangan, 2016)
The physical of paddy and milled rice qualities, physicochemical properties and the functional properties of milled rice were analyzed to study the grain characteristics of four local paddy varieties derived from West Kalimantan. The study was conducted at Post Harvest Grain Quality Laboratory, Indonesian Center for Rice Research in 2013. Method used for physical and milling quality properties followed IRRI method. Functional characteristic was analyzed using LC-MS. The observations were done in six replications. The data was analyzed for the correlation among characters. Significant correlation between characters was further analysed for regression equation. The shapes of grains of local rice varieties were slim to medium. There was correlation between paddy moisture content and head rice percentage, between damaged grain and paddy density, between yield of brown rice and yield of milled rice, and percentage of head rice, between percentage of head rice and yield of milled rice, and between empty grain and broken grain. The functional character relationship showed that Cyanidin 3 Glucosidase (C3G) content of brown rice influenced the C3G content of milled rice. â€œSanikâ€ red rice, â€œBeliahâ€ purple rice and â€œBalikâ€ black rice may be useful to be used as parent for crossing in the breeding program for functional rice varieties, due to their good quality of milled rice and their high content of C3G. The C3G is considered as anticancer, antioxidant, anti coronaria heart disease and it improves fat profiles in the blood. Therefore, colored rice is recommended to be consumed in a form of brown rice or milled rice with 80% degree milling to retain the C3G content which is beneficial for the human health.